Assessment of the Body Composition and the Loss of Fat-Free Mass through Bioelectric Impedance Analysis in Patients Who Underwent Open Gastric Bypass - Wilson Rodrigues de Freitas Junior; Elias Jirjoss Ilias; Paulo Kassab; Roberto Cordts; Paulo Gustavo Porto; Francisco Cesar Martins Rodrigues; Mohamed Ibrahim Ali Taha; Paulo Carrara; Isabella de Carvalho Aguiar; Luis Vicente Franco de Oliveira; Osvaldo Castro; Carlos Alberto Malheiros (The Scientific World Journal)
Background. Bariatric surgery is considered an effective option for the management of morbid obesity. The incidence of obesity has been gradually increasing all over the world reaching epidemic proportions in some regions of the world. Obesity can cause a reduction of up to 22% in the life expectancy of morbidly obese patients. Objective. The objective of this paper is to assess the weight loss associated with the first 6 months after bariatric surgery using bioelectric impedance analysis (BIA) for the evaluation of fat mass and fat-free mass. Method. A total of 36 morbidly obese patients were subjected to open gastric bypass surgery. The patients weight was monitored before and after the procedure using the bioelectric impedance analysis. Results. Bariatric surgery resulted in an average percentage of weight loss of 28.6% (40 kg) as determined 6 months after the procedure was performed. Analysis of the different components of body weight indicated an undesirable loss of fat-free mass along with the reduction of total body weight. Conclusion. Open gastric bypass induced a significant loss of total weight and loss of fat-free mass in patients six months after the surgery. The use of bioelectric impedance analysis resulted in an appropriate estimation of the total weight components in individuals subjected to bariatric surgery allowing a more real analysis of the variation of weight after the surgery.